Experiences of a theatre of the oppressed workshop - Subedi, Imona; Shankar, Pathiyil Ravi (Janaki Medical College Journal of Medical Science, 2018)
Theatre of the Oppressed (TO) created by the Brazilian theatre personality, Augusto Boal helps individuals deal with both external and internal sources of oppression. TO workshops are now held in many educational institutions and other settings. TO enables participants to step beyond the walls of the classroom, explore various life situations, improves the skill of both verbal and non-verbal communication, enables participants to experience various oppressors and oppressed situations and formulate strategies to deal with them. The authors describe a three day TO workshop conducted at KIST Medical College, Lalitpur, Nepal from 6th to 8th April 2012. Janaki Medical College Journal of Medical Sciences (2017) Vol. 5(2): 41-45